Recurrent, Severe Aphthous Stomatitis and Mucosal Ulcers as Primary Manifestations of a Novel STAT1 Gain-of-Function Mutation - Erdős, Melinda; Jakobicz, Eszter; Soltész, Beáta; Tóth, Beáta; Bata-Csörgő, Zsuzsanna; Maródi, László (Frontiers in Immunology, 2020)
Chronic mucocutaneous candidiasis (CMC) characterized by persistent and recurrent Candida infection of the skin, nails, and the mucose membranes has been proposed as the major infectious phenotype in patients with gain-of-function mutation of signal transducer and activator of transcription (STAT) 1. However, viral infections caused mostly by herpesviruses, and a broad range of autoimmune disorders may also be part of the clinical phenotype. We report here on a 31 years old female patient suffering from severe mucosal aphthous mucositis and ulcers and recurrent herpes simplex for decades. We found a previously unknown heterozygous sequence variant in STAT1 (c.1219C>G; L407V) affecting the DNA-binding domain of the protein in the patient and her 4 years old daughter. We found this mutation gain-of-function (GOF) by using immunoblot and luciferase assays. We detected low proportion of IL-17A-producing CD4+ T cell lymphocytes by using intracellular staining and flow cytometry. Candida-induced secretion of IL-17A and IL-22 by mononuclear cells from the patient was markedly decreased compared to controls. These data suggest that the novel mutant allele may result in impaired differentiation of CD4+ T cells to CD4+/IL-17+ cells. The clinical phenotype of the disease in this patient was unique as it was dominated primarily by severe aphthous stomatitis and ulcerative esophagitis and only partly by typical CMC resulting in diagnostic delay. We suggest that patients with severe recurrent aphthous stomatitis and esophagitis should be evaluated for STAT1 GOF mutation. Based on the broad clinical spectrum of the disease, we also suggest that CMC and CMC disease may not be an appropriate term to define clinically STAT1 GOF mutation.